Upaya Meningkatkan Minat dan Pemahaman Anak dalam Pembelajaran Al Qur’an melalui Metode Interaktif di TPA Masjid Baiturrahim, Danukusuman: Efforts to Enhance Children's Interest and Understanding in Al Qur’an Learning through Interactive Methods at Baiturrahim Mosque TPA, Danukusuman - Andika Surya Pramudiya; Nandito Aska Alfareza; Ilham Ridho Ardhana; Fathiharama S.Z; Fahrizal Galang Pratama; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The Field Practice and Professional Service (PKLPP) activity at Taman Pendidikan Al-Qur’an (TPA) Masjid Baiturrahim, Danukusuman, was conducted to improve children’s ability to read and memorize the Qur’an as well as to instill Islamic values from an early age. Students were actively involved in the learning process by applying various methods such as delivering engaging materials, holding interactive quizzes, conducting ice-breaking activities, and giving rewards to enhance learning motivation. The results indicated an increase in children’s enthusiasm and participation during the Qur’an learning sessions. Furthermore, this activity provided practical experience for students in developing teaching skills within a community setting. This program is expected to support the formation of children’s religious character and improve the quality of learning at the TPA.